Growth and Feeding Ecology of Dnieper chub Petroleuciscus borysthenicus (Kessler, 1859) in Şahinkaya Reservoir, an Artificial Water Body of an Island Ecosystem (Gökçeada, Turkey) - Gülşah Saç; Sevan Ağdamar (Journal of Advanced Research in Natural and Applied Sciences)
Bio-ecological studies and life-history traits of small-bodied fishes are critical for the understanding of their ecolog-ical role as well as the assessment of their position and continuity in the ecosystems. The current study goals to present initial data on growth and feeding habit of small-bodied Petroleuciscus borysthenicus inhabited in an island ecosystem (Gökçeada, Turkey). During the seasonally sampling surveys from May 2020 to January 2021, a total of 163 specimens were collected from Şahinkaya Reservoir using electrofishing. SL and W values of samples ranged from 2.6–10.0 cm and 0.32–25.68 g, respectively. LWR and K values were estimated for all specimens as W=0.017×SL3.114 (r=0.988) and 2.04 (±0.28), respectively. F:M sex ratio was calculated as 1:1.33 with no signifi-cant difference from the ratio of 1:1 (2=0.02; p>0.05). Diet of the species comprised of ten different food items. Plant (63.6%) was the most preferred food item from the point of frequency of occurrence (F%), pursued by Dip-tera (31.8%) and Odonata (12.7%). According to IRI (%) values of food items, Diptera was the dominant food item in all seasons. B and BA values were estimated as 3.18 and 0.24, respectively. The results showed that P. borysthenicus was more selective on conveniently accessible food materials in the environment and its food pref-erence was affected by seasonal food supply.